e-Learning technologies and evidence-based assessment approaches [ - Lajbcygier, Paul; Spratt, Christine (Advances in information and communication technology education (AICTE) series, 2009)
"This book aims to provide readers with a variety of contemporary solutions to identified educational problems of practice related to the assessment of student learning in e-learning environments"--Provided by publisher.